Critical analysis of the law of terrorism in Malaysia / Firda Elena Omardin, Farazwin Haxdy and Nor'aamirah Shafie - Omardin, Firda Elena; Haxdy, Farazwin; Shafie, Nor'aamirah (2005)
The issues of the encroachment of the fundamental liberties have been the main problem arising from the inadequacies of the law of terrorism in Malaysia. Before the amendment of the law in 2003, ISA is identified to encroach a person's right to a hearing and detention without just cause. The government made a progressive step in amending both substantive and procedural law in order to occupy the loopholes and lacuna in the law of terrorism in Malaysia, the aim of this study is to examine the legal implications and justifications to the amendment and to identify the policies underlying the amendment to the law. In accordance with the theme of the study, the legal chapters (Chapter 3 and Chapter 4) provide an account to the legal implication and justifications of the amendment. This research also criticizes in the effects of the implementation of the new law. Many problems may arise, like the encroachment of fundamental liberties, infringement of privacy, extensive powers of arrest by the police, vague provisions relating to the definition of "providing facilities" from the new law would cause injustice to the people at large. The issue on the duty to report, dealing with terrorist property, false reporting, and encroachment into Legal Profession Act will also be looked upon in greater detail. The research will contribute to our understanding on the new law on terrorism to deter terrorism offences in Malaysia. It also provides the insights to the recommendations to improve the law on terrorism.